Cyclic pushover of RC columns using rigid body spring discrete element method - Nunez, Krishia Lynne M. (College of Engineering, University of the Philippines Diliman, 2016)
In this study, the Rigid Body Spring Discrete Element Method (RBS-DEM) was used to perform cyclic pushover tests on RC columns. Three hinge models were validated in this study. These three hinge models are the XZSF (Xu Zhang Shear-Flexure) Hinge Model, the FMXZS (Fiber Modelling and Xu Zhang Shear) Hinge Model and the FMBDS (Fiber Modelling and Bilinear Diagonal Springs) Hinge Model. The hinge models were validated by performing monotonic and cyclic pushover tests and comparing the pushover curves and force displacement plots obtained from the simulation to the hysteresis plots of the columns based from past experiments. Three columns for each type of failure for RC columns were selected. A total of 9 columns obtained from the PEER Structural Performance Database were used for the validation. The results showed that the one out of the three hinge models used was able to simulate the response of flexure-critical columns for the monotonic pushover tests. None of the three hinge models tested were able to simulate the response of the columns for the cyclic pushover tests.